The Underpinning of the Yoruba View of Hairstyle - Agwuele, Augustine (The Symbolism and Communicative Contents of Dreadlocks in Yorubaland, 2016)
It is important to reiterate that the discussion of this book is mainly centered on the everyday lives of the Yoruba people. It is concerned with the way in which their views of a matured male Yoruba person with cornrows and dreadlocks hairstyles, though mere hairstyles, are revealed in casual interactions to be ominous. The Yoruba view of the hair is tied to their view of the head as particularly sacred, particularly deterministic of an individual’s earthly existence, and requiring particularly protections by all means.